ESTIMATION OF THE POROSITY OF PORTLAND CEMENT PASTES USING BACKSCATTERED ELECTRON IMAGE - MELLAS, M.; MEZGHICHE, B.; ASH J., E. (Courrier du Savoir; Vol. 4 (2003): Courrier du Savoir)
Microscopy plays an important role in the examination of cementitious materials. Electron-optical techniques allow examination of microstructural details. The increased application of scanning electron microscopy in cement and concrete investigations has brought attention to the estimation of the porosity. Backscattered Electron image has been established as a method for quantitative analysis of hardened cement paste. This paper describes work and its application to Ordinary Portland cement paste. Results show that the technique can be used to determine the porosity of Portland cement pastes. The success of these investigations is, influenced by the type and quality of specimen preparation. In particular, backscattered electron and Xray imaging modes are influenced by the specimen surface characteristics, with the ideal surface being highly polished. The technique can be a powerful tool to determine this essential factor of durability in concrete materials. Keys words: porosities, cement paste, strength, Scanning electron microscope, methanol exchange.